The Adoption of Multiplayer Online Battle Arena to Introduce Wayang Character - Andre Andre (Journal of Games, Game Art, and Gamification, 2021)
Wayang is considered a cultural heritage that has been passed down from generation to generation in Indonesia. However, the younger generation known as digital natives shows a lack of motivation and interest in Wayang. Therefore, it became an important matter to introduce traditional Wayang to younger audiences in engaging formats. This paper proposes an adaptation of the multiplayer online battle arena or known as MOBA. This type of multiplayer game for the mobile market is gaining high popularity among the young generation because it embraces quick-paced, strategic, and intense battle scenes. We called our game "Wayang Tarung" or "Wayang Battle" in English. Furthermore, the game has several features supporting the narrative of wayang characters, such as simple digital motion comics and character briefing between loading screens. A mechanic-dynamic-aesthetic framework (MDA) is used as a guideline to assure the game has engaging gameplay. Since the game runs asymmetrically, the starting condition for both players must be considered. Therefore, we also apply a game balancing strategy to ensure that each Wayang character has weak and strong points. In addition, we were adapting artificial intelligence from the Clash Royale game to dictate autonomous character behavior. The implementation of the Wayang Tarung game has been evaluated using a heuristic testing method adapted from the norman Nielsen heuristic usability. We also conducted a direct observation in a controlled-lab condition and gathered the data using a pre-post test that evaluated player knowledge of Wayang's character. Based on the excellent mark pre-post test result, we believe that adopting the multiplayer game platform in introducing wayang characters to the young generation has enriched prominent to explore further.